Do You Choose Him or Does He Choose You? - Analyzing Character Archetypes in Otome Games - Pawlowski, Camila; Mota, Rosilane Ribeiro da (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2022: Anais Estendidos do XXI Simpósio Brasileiro de Jogos e Entretenimento Digital, 2022)
The relationship between fiction and humanity is long-established and can create strong affective bonds. This connection can also be seen in digital games, especially otome games. In this sense, this research was developed in order to obtain a richer understanding of players’ bonds with character tropes from otome games through the archetypal typology developed by Margareth Mark and Carol Pearson, and was able to identify that the analyzed tropes are connected to at least one of the archetypes defined by the authors. This study’s findings can contribute to the understanding of parasocial relationships between fictional characters and humans, and, additionally, aid game developers in creating more intricate characters infused with the power of archetypes.